Physiotherapists' Experiences with and Perspectives on Implementing an Evidence-Based, Chronic Pain Self-Management Programme in Primary Health Care: A Qualitative Study. - Brewer, Emily; Carnevale, Nicole; Ducsharm, Melissa; Ellis, Nicole; Khan, Mohammed; Vader, Kyle; Miller, Jordan (Physiotherapy Canada)
Purpose: Evidence suggests that a physiotherapist-led chronic pain self-management programme in primary health care (PHC) improves function for people living with chronic pain; however, implementing a new approach to care can be difficult. In this study, we sought to understand the experiences of physiotherapists who had implemented the ChrOnic pain self-ManageMent support with pain science EducatioN and exerCisE (COMMENCE) programme; its perceived barriers, facilitators, benefits, and drawbacks; and how the physiotherapists tailored the programme to their own clinical contexts. Method: This interpretive description qualitative study used semi-structured interviews with physiotherapists who had implemented the COMMENCE programme in PHC. Results: Themes from 11 interviews included experiences of personal and professional growth, increasing confidence with experience, and changing the culture of pain management. Barriers and drawbacks to implementation included resource intensiveness, balancing programme demands with other clinical work, and challenges with patient attendance and participation. Facilitators included training, programme design and materials, supportive teams, and previous knowledge. Benefits included offering group and individualized support, evidence-based content, and sparking interest in learning more about pain management. The participants made small changes to tailor the programme content and delivery to their context. Conclusions: This study provides a rich understanding of the experiences, barriers, facilitators, benefits, drawbacks, and tailoring related to the COMMENCE programme in PHC. The results will facilitate future implementation of this intervention in PHC settings.